Labour market institutions and the personal distribution of income in the OECD - Daniele Checchi; Cecilia García-Pe\~nalosa (Center for Economic Studies and ifo Institute (CESifo), 2005)
We examine the determinants of differences across countries and over time in the distribution of personal incomes in the OECD. The Gini coefficient of personal incomes can be expressed as a function of the wage differential, the labour share, and the unemployment rate, hence labour market institutions are an essential determinant of the distribution of income, although the sign of their impact is ambiguous. We use a panel of OECD countries for the period 1970- 96 to examine these effects. We find, first, that the labour share remains an important determinant of overall inequality patterns, and, second, that stronger unions and a more generous unemployment benefit tend to reduce income inequality. High capital-labour ratios also emerge as a strong equalising factor, which has in part offset the impact of increasing wage inequality on the US distribution of personal incomes.
Keywords: D33; D31; 330; income inequality; labour share; trade unions; Einkommensverteilung; Arbeitsmarktflexibilisierung; Lohnstruktur; Arbeitslosigkeit; Lohnquote; Kapitalintensität; Schätzung; OECD-Staaten